Foot tapping and unilateral vertical jump performance in athletes after knee surgery: an explorative cross-sectional study - Kurz, E.; Schwesig, R.; Pröger, S.; Delank, K.-S.; Bartels, T. (BMC Sports Science, Medicine and Rehabilitation, 2022)
Background Guiding athletes through the rehabilitation process and judging the time at which return to sports can be enabled after anterior cruciate ligament (ACL) injuries are still challenging processes. The purpose of this explorative cross-sectional study was to retrospectively compare unilateral vertical jump as well as vertical foot tapping outcomes in athletes returned to sports after ACL reconstruction (ACLR) with uninjured athletes.